Memórias e saberes construtivos tradicionais nas comunidades quilombolas do Barro Preto, Boa Vista, Indaiá e Macuco – Minas Gerais - Maxiliano Perdigão dos Santos (2022)
The understanding concerning traditional constructive know-how plays an important role in vernacular architecture studies. It goes beyond the built materiality itself, because through it we have the opportunity to discern the historical and cultural trajectory that cames with this architecture. From this historical, cultural and technical perspective, the thesis discusses the processes that form the traditional constructive knowledge of the quilombola communities of Barro Preto, Boa Vista, Indaiá and Macuco, located in Minas Gerais - Brazil. Despite the scarcity of constructions built with the technique recognized by communities – which is wattle and daub, the people who are part of them have a lot to offer in terms of knowledge about their traditional know-how. The main objective of the work was to hear from the people of these communities current and historical information about the processes that characterize their know-how in vernacular construction. Based on an interdisciplinary methodology that draws on academic and popular knowledge, the research was conducted, mainly, through an approach inspired by the ethnographic sensibility derived from anthropology. At the end of the work, it is possible to affirm that the adoption of this work methodology, without the definition of a hierarchy between the academic fields studied, proved to be not only efficient, but fundamental for the accomplishment of this work. Through the construction of layers of information throughout the research work, it was possible to identify that: contrary to the common sense, the African people who were brought enslaved to Brazil had technical knowledge in several areas that contributed for the formation of the country; the communities have several people who still master traditional building techniques; some groups are interested in keeping the constructive tradition alive. Among the challenges of preserving traditional knowledge, the following are noteworthy: the lack of interest of the new generations; the high cost of good quality wood suitable for construction; the difficulty in bringing together many people to promote joint construction efforts. In addition to specific information, the work carried out helped to identify other potential fields of research and opportunities for university extension activities – in the same community environment, focused on areas such as archeology, sociology, anthropology, history, tourism, arts, among others.